2011
DOI: 10.1007/s13277-010-0147-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of vascular density and area in colorectal carcinoma using different markers and comparison with clinicopathologic prognostic factors

Abstract: Analysis of blood and lymphatic vessel in colorectal cancer is controversial in the literature, possibly due to variations in the methods of analysis. In this study, it was aimed to search for a reliable approach in the quantification of angio- and lymphangiovascular density and area as a prognostic factor and to compare such vessel counts in normal mucosa, adenomas and cancer. A retrospective study was performed on 60 sporadic colorectal cancer, 30 colorectal adenomas, and 10 colorectal non-neoplastic lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The CD34 expression was correlated with adenomas containing severe dysplasia and large adenomas (more than 1 cm) and the significant association of this marker with tumor grade, lymphovascular invasion and lymph node involvement in colorectal carcinoma were also approved (Qasim et al, 2012). Similarly, in a retrospective study, Moreira et al (2011) evaluated the vascular density through immunohistochemical analysis in colorectal carcinoma and showed that the CD34 expression in the central area, cancer is associated with relapse, metastasis and survival rate. The study showed that the incidence of CD34 in the inner area of colorectal carcinoma tumors has the prognostic value in this cancer.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The CD34 expression was correlated with adenomas containing severe dysplasia and large adenomas (more than 1 cm) and the significant association of this marker with tumor grade, lymphovascular invasion and lymph node involvement in colorectal carcinoma were also approved (Qasim et al, 2012). Similarly, in a retrospective study, Moreira et al (2011) evaluated the vascular density through immunohistochemical analysis in colorectal carcinoma and showed that the CD34 expression in the central area, cancer is associated with relapse, metastasis and survival rate. The study showed that the incidence of CD34 in the inner area of colorectal carcinoma tumors has the prognostic value in this cancer.…”
Section: Discussionmentioning
confidence: 91%
“…The CD34 expression is significantly associated with adenomas containing severe dysplasia and large adenomas (more than 1 cm) (Qasim et al, 2012;Sidney et al, 2014). In many other immunohistochemical studies, the expression of this protein is used as a reliable marker to evaluate cancer tumors including: colon (Moreira et al, 2011;Sidney et al, 2014), blood (Borowitz et al, 1990), liver (Borowitz et al, 1990), penile (Martins et al, 2002), lung (Van de Rijn et al, 1994) and trichilemmal (Chaichamnan et al, 2010) cancers. The studies have shown the correlation between CD34 with many clinicopathologic factors as well as the ability of this marker as a prognostic factor.…”
Section: Asian J Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies were conducted to determine whether lymphangiogenesis is associated with these genetic alterations. In 2011, Moreia et al23 performed a retrospective study including 10 colorectal non-neoplastic lesions, 30 colorectal adenomas and 60 sporadic CRC tumors and found that LMVD increased significantly and sequentially from non-neoplastic tissues to adenomas and cancerous tumors. Another study showed that LMVD was significantly higher in adenomas from patients with carcinoma than those in patients without cancer 24.…”
Section: Lymphangiogenesis May Be An Early Event In Crc Developmentmentioning
confidence: 99%
“…Numerous studies have used the expression of this protein as a reliable marker in cancerous tumors by immunohistochemistry. For example, in GC (Dvorak, 1986;Hayashi, 1975), colon (Moreira et al, 2011;Qasim et al, 2012), liver (Cui et al, 1996), blood (Borowitz et al, 1990) and lung (Van de Rijn et al, 1994), the CD34 expressions have been used for diagnostic examination, as well as the relationship between these markers and clinico-pathologic factors.…”
Section: Introductionmentioning
confidence: 99%